Кластероутворення фулеренів у рідинній системі C70–N-метил-2-піролідон–толуол - Bulavin, L. A.; Nagorna, T. V.; Kyzyma, O. A.; Chudoba, D.; Ivankov, O. I.; Nagornyi, A. V.; Avdeev, M. V. (Publishing house "Academperiodika", 2018)
The structural behavior of the liquid system based on a C70 in an N-methyl-2-pyrrolidone–toluene mixture has been analyzed, by using the small-angle neutron scattering method. The experimental results testify to the selective solvation in the system. The corresponding mechanisms have been discussed.